Composite battery diaphragm as well as preparation method and application thereof
By using organic and inorganic composite coating of polyethylene oxide, scandium oxide and titanium dioxide on the lithium-ion battery separator, the problem of insufficient thermal stability of the separator and electrolyte affinity is solved, and the safety of the battery is improved. performance.
Patent Information
- Application Number
- CN202411145489.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-20
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-08-20
AI Technical Summary
The poor thermal stability, insufficient wettability and low ionic conductivity of the lithium-ion battery separator limit the electrochemical performance and safety of the battery.
Organic and inorganic composite modified materials are used as the coating layer, including polyethylene oxide, scandium oxide and titanium dioxide, to form nanoparticles by mixing and doping, thereby improving the thermal stability, electrolyte affinity and ionic conductivity of the separator.
It effectively improves the thermal stability of the separator and the electrolyte affinity, reduces the interface impedance, reduces the formation of lithium dendrites, and improves the safety and performance of the battery.
Smart Images

Figure BDA0005002081740000121
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a composite battery separator and a preparation method and application thereof. Background Art
[0002] Currently, secondary lithium-ion batteries (LIBs) are widely used in wearable devices, electric vehicles, and industrial energy storage. However, the rapid development of electric vehicles has put forward higher requirements on battery safety and energy density. In this regard, the separator plays a vital role as a key component of the battery. The most common lithium-ion battery separators are made of polyolefin materials, such as polypropylene (PP), polyethylene (PE) and their blends. Although conventional lithium-ion battery separators have excellent chemical stability and high mechanical strength, they have defects such as poor electrolyte wettability, low ionic conductivity and poor thermal stability, which seriously limit the electrochemical performance and safety of lithium-ion batteries.
[0003] Specifically, the preparation methods of polyolefin separators are mainly divided into two processes: dry process and wet process. Among them, the dry process, also referred to as the melt stretching method, first needs to heat the polyolefin resin to a molten state, then prepare a crystalline film by extrusion, and then anneal to form a highly oriented multilayer non-porous structure, and finally heat-stretch under high temperature and low stretching rate conditions, so that the regularly arranged chips are separated and form slit-like micropores with small pore size and uniform distribution. The wet process, also referred to as the thermally induced phase separation method, first heats the polyolefin resin and other additives to a molten state, mixes them evenly, and forms a non-porous film by extrusion, then cools them by casting and stretches them in two directions, uses volatile solvents to extract the additives and form micropores, and finally heat sets them. Although polyolefin separators are relatively mature in development and application, polypropylene and polyethylene themselves have low melting points (PE melting point 110°C, PP melting point 150°C), and the surface is non-polar, which leads to poor thermal stability and wettability of polyolefin separators, which limits their application in high-performance lithium-ion batteries.
[0004] Taking polyolefin diaphragms as an example, this type of diaphragm is widely used in the field of secondary lithium-ion batteries, but it has at least the following defects: 1) Poor thermal stability. Polyolefin diaphragms are prone to shrinkage or melting at high temperatures, which may lead to thermal runaway or short circuit inside the battery, affecting battery safety; 2) Poor wettability. The polarity of the polyolefin diaphragm does not match the polarity of the organic electrolyte, and the electrolyte has poor wettability on the diaphragm, which seriously affects the cycle performance of the lithium-ion battery; 3) Low ionic conductivity and large internal resistance of the battery, which cannot meet the high-rate charging and discharging requirements of power cells.
[0005] The current solutions to the above problems mainly include: 1) organic coating, coating a water-based PVDF or PMMA adhesive layer on one or both sides of the polyolefin diaphragm base film, which effectively improves the wettability of the diaphragm and improves the adhesion between the diaphragm and the pole piece through the adhesive layer; 2) inorganic coating, using inorganic nanoparticles to coat both sides of the polyolefin diaphragm after treatment. The use of inorganic ceramic particles with high specific surface area and good heat resistance can make the diaphragm have better hydrophilicity and higher thermal stability. However, inorganic coatings have the defect of being easy to fall off after being heated, and the mechanical properties of organic polymer coatings are poor.
[0006] In view of this, there is an urgent need to develop a new type of diaphragm with good thermal stability, high electrolyte affinity and high ion conductivity, and the present invention is specially proposed. Summary of the invention
[0007] The first purpose of the present invention is to provide a composite battery separator, which adopts an organic-inorganic composite modified material as a coating layer to solve the technical problems existing in the existing inorganic coating or organic coating. It is mainly used to solve the technical problems that the polyolefin separator of lithium-ion batteries has low affinity with the electrolyte, poor thermal stability, and easy formation of lithium dendrites on the surface that affect the battery cycle safety, thereby providing a new separator that takes into account the advantages of both inorganic coating and organic coating.
[0008] The second object of the present invention is to provide a method for preparing the composite battery separator, which is simple and easy to implement and can be mass-produced.
[0009] A third object of the present invention is to provide a secondary battery.
[0010] A fourth object of the present invention is to provide an electrical device.
[0011] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0012] A composite battery separator comprises a base film and a coating loaded on at least one side of the base film; the coating comprises an organic component, an inorganic component and a functional component; wherein the organic component comprises polyethylene oxide, and the inorganic component comprises scandium oxide and titanium dioxide.
[0013] A method for preparing the composite battery separator comprises the following steps:
[0014] A mixed dispersion of scandium oxide and titanium dioxide is prepared, and then subjected to a temperature treatment to obtain a doped inorganic powder; the doped inorganic powder and polyethylene oxide are fully mixed in an organic solvent to obtain a composite material;
[0015] The composite material and the functional component are fully mixed in water to obtain a composite slurry; the composite slurry is coated on at least one side of a base film, and then vacuum dried to obtain a composite battery separator.
[0016] A secondary battery comprises the composite battery separator.
[0017] An electrical device comprises the secondary battery.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] In the present invention, the polar polymer polyethylene oxide of the organic component can effectively improve the wettability, thermal stability and mechanical properties of conventional polyolefins. In the present invention, titanium dioxide has the advantages of being non-toxic, stable in performance, and easy to control in preparation. It can improve the thermal stability of the diaphragm and the wettability of the electrolyte, and can absorb some impurity electrolytes, which helps to reduce the interface impedance between the diaphragm and the electrode; at the same time, titanium dioxide has good compatibility with the electrolyte, which can promote the transportation of lithium ions and improve the ionic conductivity of the diaphragm. It is an ideal organic polymer diaphragm modification material; in addition, the present invention introduces titanium dioxide into the diaphragm to reduce inter-particle stress and improve the stability of the battery. Furthermore, in the present invention, scandium oxide is doped with titanium dioxide to form oxygen vacancies, which can effectively adsorb lithium ions and make lithium ions deposit evenly, effectively reducing the formation of lithium dendrites on the surface of the diaphragm. Furthermore, the present invention mixes nano-scale inorganic metal materials and organic component PEO and then coats them on the base film. While improving the thermal stability, electrolyte affinity and ion conductivity of the diaphragm, the nanoparticles formed by mixed doping of scandium oxide and titanium dioxide can effectively improve the uneven pore distribution on the surface of the PP diaphragm and reduce the formation of lithium dendrites. DETAILED DESCRIPTION
[0020] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but those skilled in the art will appreciate that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. Those who do not specify specific conditions in the embodiments are carried out according to conventional conditions or conditions recommended by the manufacturer. Those who do not specify the manufacturer for reagents or instruments used are conventional products that can be purchased commercially. In addition, the terms "one", "two", and "1" are only used for descriptive purposes and cannot be interpreted as indicating or implying relative importance.
[0021] The first object of the present invention is to provide a composite battery separator, comprising a base film and a coating loaded on at least one side of the base film; the coating comprises an organic component, an inorganic component and a functional component; wherein the organic component comprises polyethylene oxide (PEO), and the inorganic component comprises scandium oxide (Sc2O3) and titanium dioxide (TiO2).
[0022] As a preferred embodiment, the base film includes a polyimide (PI)-polypropylene (PP) composite film; it is understandable that the composite film is prepared by combining microspherical polyimide and polypropylene.
[0023] As a preferred embodiment, the porosity of the base film is 48% to 55%; in some more preferred embodiments, the porosity is 51%.
[0024] As a more preferred embodiment, for the polyimide-polypropylene composite film, the usage ratio of polyimide to polypropylene is (1-1.5):2.
[0025] As a more preferred embodiment, the thickness of the polyimide-polypropylene composite film is 12 μm to 24 μm.
[0026] As a preferred embodiment, the usage ratio of the organic component to the inorganic component is (3-10):(10-20) by mass.
[0027] As a preferred embodiment, the thickness of the coating is 2 μm to 6 μm; it is understandable that when the coating is double-sided coated, the thickness of each layer of the coating is independently 2 μm to 6 μm.
[0028] As a preferred embodiment, the molecular weight of the polyethylene oxide is 2*10 6 ~6*10 6 In some more preferred embodiments, the molecular weight is selected from 4*10 6 .
[0029] As a preferred embodiment, the usage ratio of the scandium oxide to the titanium dioxide is (2-5):(20-30) by mass.
[0030] As a preferred embodiment, the functional component includes at least one of a dispersant, a thickener, a wetting agent and a binder. In some more preferred embodiments, the functional component includes a dispersant, a thickener, a wetting agent and a binder at the same time.
[0031] As a more preferred embodiment, the functional components include the following components in parts by weight: 0.55 to 2.5 parts of dispersant, 2.5 to 12 parts of thickener, 0.2 to 0.8 parts of wetting agent, and 2 to 5 parts of adhesive.
[0032] As a more preferred embodiment, the mass ratio of the sum of the mass of the organic component and the inorganic component to the mass of the functional component is (25-40):(5.25-20.3).
[0033] As a more preferred embodiment, the dispersant includes at least one of polyvinyl pyrrolidone (PVP), polyacrylate (PAA), polyacrylamide (PAM) and polyacrylic acid.
[0034] As a more preferred embodiment, the thickener includes at least one of hydroxymethyl cellulose (CMC), hydroxymethyl cellulose sodium (CMCNa), hydroxypropyl methyl cellulose (HPMC), and methyl cellulose (MC).
[0035] As a more preferred embodiment, the wetting agent includes at least one of sodium butylnaphthalene sulfonate or sodium alkyl sulfate.
[0036] As a more preferred embodiment, the adhesive includes at least one of polyacrylic acid or polyacrylonitrile.
[0037] The second object of the present invention is to provide a method for preparing the composite battery separator, which mainly includes the following four steps (1) to (4).
[0038] (1) A mixed dispersion of scandium oxide and titanium dioxide is prepared, and then subjected to a temperature treatment to obtain a doped inorganic powder.
[0039] As a preferred embodiment, the scandium oxide dispersion is first prepared, and then the titanium dioxide is added thereto, and the mixture is fully mixed to obtain the mixed dispersion.
[0040] As a preferred embodiment, the solvent of the mixed dispersion is water; in some optional embodiments, the solid content of the mixed dispersion is 0.08 g / mL to 0.2 g / mL.
[0041] As a preferred embodiment, the preparation of the mixed dispersion includes a step of sufficient mixing, and the sufficient mixing includes but is not limited to oscillation, stirring, centrifugation, ultrasound, etc.
[0042] As an optional implementation, the scandium oxide is added to a solvent, stirred for 30 to 60 minutes, and then ultrasonicated to obtain a dispersion of the scandium oxide; the titanium dioxide is added to the scandium oxide dispersion, and stirred for 40 to 60 minutes to obtain the mixed dispersion.
[0043] As a preferred embodiment, the temperature of the heating treatment is 160°C to 200°C, including but not limited to any one of 160, 165, 170, 175, 180, 185, 190, 195, 200 (°C) or a numerical range composed of any two of them, and the holding time of the heating treatment is 2h to 4h, including but not limited to any one of 2, 2.2, 2.4, 2.5, 2.6, 2.8, 3, 3.2, 3.4, 3.5, 3.6, 3.8, 4 (h) or a numerical range composed of any two of them.
[0044] As a preferred embodiment, after the temperature raising treatment, the method further comprises: washing, solid-liquid separation and drying.
[0045] (2) The doped inorganic powder and polyethylene oxide are fully mixed in an organic solvent to obtain a composite material.
[0046] As a preferred embodiment, after the thorough mixing, washing, solid-liquid separation and drying are also included. In some optional embodiments, the washing medium is acetone.
[0047] As a preferred embodiment, the doped inorganic powder is first fully dispersed in a first organic solvent to obtain a first dispersion; the polyethylene oxide is then fully dispersed in a second organic solvent to obtain a second dispersion; the first dispersion and the second dispersion are fully mixed to obtain a composite material.
[0048] As a more preferred embodiment, the first solvent includes N-methylpyrrolidone (NMP), and the second solvent includes acetone.
[0049] As a more preferred embodiment, similar to step (1), any of the sufficient mixing involved in this step includes but is not limited to oscillation, stirring, centrifugation, ultrasound, heat treatment, bubbling, etc.
[0050] As a more preferred embodiment, the mass ratio of the doped inorganic powder to the first organic solvent is (1-2):(6-10).
[0051] As a more preferred embodiment, the mass ratio of the polyethylene oxide to the second organic solvent is (3-10):(45-80).
[0052] As an optional implementation, the doped inorganic powder is first fully dispersed in a first organic solvent, and ultrasonically treated for 0.5 h to 3 h to obtain a first dispersion; the polyethylene oxide is then fully dispersed in a second organic solvent, and stirred in a closed container at 50°C to 80°C for 5 h to 8 h, and then ultrasonically treated to obtain a second dispersion; the first dispersion and the second dispersion are fully mixed, and stirred for 5 h to 8 h to obtain a composite material.
[0053] (3) The composite material and the functional component are fully mixed in water to obtain a composite slurry.
[0054] As a preferred embodiment, the sufficient mixing is performed by high-speed stirring and dispersing, and the rotation speed of the high-speed stirring and dispersing is 300 rpm to 500 rpm.
[0055] As a preferred embodiment, the step of further comprising any one or more of screening, iron removal and defoaming is performed after the sufficient mixing.
[0056] As a preferred embodiment, in the composite slurry, the mass proportion of water is 40% to 70%. Those skilled in the art can adjust the solid content of the coating slurry according to the actual functional requirements of the coating process.
[0057] (4) The composite slurry is coated on at least one side of a base film, and then vacuum dried to obtain a composite battery separator.
[0058] As a preferred embodiment, the coating is performed by micro-concave roller coating or slit extrusion coating.
[0059] As a preferred embodiment, the vacuum drying temperature is 65° C. to 75° C., and the vacuum drying time is 6 h to 8 h.
[0060] The third object of the present invention is to provide a secondary battery, including the composite battery separator. It is understandable that, in addition to the composite battery separator, the secondary battery should include positive and negative electrodes, electrolyte, and other necessary or unnecessary functional elements or packaging components, etc., and those skilled in the art can make any selection and combination thereof; when the composite battery separator of the present invention is included in the secondary battery, whether or not other separator functional parts are used in the secondary battery, it can be regarded as an embodiment of the present invention.
[0061] The fourth object of the present invention is to provide an electrical device, including the secondary battery. The electrical device can be any device or apparatus that relies on electric energy to work or operate, including but not limited to new energy vehicles, building electrical equipment, industrial electrical appliances, household and agricultural electrical appliances, etc. When the secondary battery is included, any electrical device equipped with the secondary battery can belong to an embodiment of the present invention.
[0062] Example 1
[0063] S1: Add 25g of nano-TiO2 particle powder into 250mL of pure water, stir for 45min, and perform ultrasonic dispersion for 65min to obtain a TiO2 dispersion; then slowly add 3g of Sc2O3 thereto, stir for 50min, then heat to 180℃ and keep the temperature for reaction for 3h; after the reaction, wash, centrifuge and dry the reaction product to obtain Sc2O3-doped TiO2 particle powder.
[0064] S2: Add 15 g of the nanopowder obtained in S1 to 100 g of N-methylpyrrolidone, stir and then perform ultrasonic treatment for 3 hours to obtain a modified nanomaterial dispersion in a dispersed state; then slowly add 3 g of PEO powder to 80 g of acetone, seal and stir at 70°C for 8 hours and perform ultrasonic dispersion to obtain PEO slurry; slowly add the PEO slurry to the modified nanomaterial dispersion, stir for 8 hours, wash, centrifuge and dry the obtained dispersion to obtain an organic-inorganic hybrid material.
[0065] S3: Add 25g of the organic-inorganic hybrid material obtained in S2 and 0.5g of a dispersant (PVP) into pure water for mixing and stirring, then add 5g of a thickener (CMC), 0.5g of a wetting agent (sodium butylnaphthalenesulfonate) and 2.4g of a binder (polyacrylic acid), and then perform high-speed dispersion, screening, iron removal and defoaming treatment in sequence to obtain a mixed coating slurry.
[0066] S4: The mixed coating slurry obtained in S3 is coated on one side of a PI-PP composite base film with a thickness of 14 μm by slit extrusion coating, with a coating thickness of 4 μm, and vacuum dried at 70°C for 8 hours to obtain a composite material coated diaphragm with a thickness of 18 μm.
[0067] Example 2
[0068] It is basically the same as Example 1, except that:
[0069] In step S1: the amount of nano-TiO2 particle powder used is 20g, and the amount of Sc2O3 used is 2g.
[0070] Example 3
[0071] It is basically the same as Example 1, except that:
[0072] In step S1: the amount of nano-TiO2 particle powder used is 30g, and the amount of Sc2O3 used is 5g.
[0073] Example 4
[0074] It is basically the same as Example 1, except that:
[0075] In step S2: the amount of nano powder used is 10 g, and the mass of PEO powder is 5 g.
[0076] Example 5
[0077] It is basically the same as Example 1, except that:
[0078] In step S2: the amount of nano powder used is 20 g, and the mass of PEO powder is 10 g.
[0079] Example 6
[0080] It is basically the same as Example 1, except that:
[0081] In step S3: the type of dispersant is replaced by PAA, the type of thickener is replaced by HPMC, the type of wetting agent is replaced by sodium alkyl sulfate, and the type of binder is replaced by polyacrylonitrile.
[0082] Example 7
[0083] It is basically the same as Example 1, except that:
[0084] In step S4: the mixed coating slurry obtained in S3 is coated on both sides of the PI-PP composite base film; wherein the coating thickness on each side is 4 μm, and finally a composite material coated diaphragm with a thickness of 22 μm is obtained.
[0085] Comparative Example 1
[0086] It is basically the same as Example 1, except that:
[0087] In step S4: the PI-PP composite base film is replaced with a PP film of the same thickness.
[0088] Comparative Example 2
[0089] It is basically the same as Example 1, except that:
[0090] Step S1 is eliminated, and in step S2 only operations related to PEO powder are retained; that is, only organic components are used in the coating slurry, and the inorganic components of Sc2O3-doped TiO2 particle powder are eliminated.
[0091] Test example
[0092] (1) Air permeability: Cut three pieces of membrane from the film roll at an interval of 150 mm in the longitudinal direction. Take a sample of each piece with a size of 100 mm × 100 mm. Place the membrane in the test head of the air permeability tester for air permeability test. The average value of the three test results is taken as the air permeability value of the membrane.
[0093] (2) Heat shrinkage rate: Cut three 100mm×100mm square membranes in the longitudinal direction of the membrane roll. When cutting the membranes, one edge of the membrane roll should be parallel to at least one edge of the membrane, and the maximum deviation angle should not exceed 5°; put the stainless steel plate and two quantitative filter papers in the middle of the oven, control the temperature so that the stainless steel plate and the filter papers reach (105±1)℃, mark the longitudinal and transverse directions of the test membrane, and then place the membrane flat on the quantitative filter paper on the stainless steel plate in the middle of the blast thermostatic box. After completion, press it with another quantitative filter paper, close the thermostatic box door, start counting the time, and keep it at 105℃ for 1h±5min. After heating, take out the membrane, wait for the membrane to return to room temperature, and measure the longitudinal and transverse marking lengths again. Calculate the longitudinal and transverse shrinkage rates of the membrane respectively, and take the average of the three test results as the heat shrinkage rate of the membrane.
[0094] (3) Liquid absorption rate: Cut 3 square diaphragms of 100 mm × 100 mm in the longitudinal direction of the film roll, bake the samples in a drying oven at 105±2°C to constant weight, then cool to room temperature and record their mass m1; place the samples in a container with sufficient electrolyte to ensure that the samples are completely immersed, and soak them at a constant temperature of 23°C for 24 hours. Take out the soaked samples, gently wipe off the surface moisture, weigh them immediately, and record their mass m2; calculate the liquid absorption rate = (m2-m1) / m1×100%.
[0095] Table 1
[0096]
[0097] It can be seen from Table 1 that the thermal shrinkage and liquid absorption rate of the diaphragm samples in the embodiment are significantly higher than those in the comparative example, indicating that the PEO@TiO2 composite material coated diaphragm of the present invention can effectively improve the problems of poor thermal stability of the polyolefin diaphragm and insufficient electrolyte affinity, and ensure the performance and safety of the battery product.
[0098] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A composite battery separator, characterized in that: The composite battery separator includes a base film and a coating layer supported on at least one side of the base film; The coating comprises an organic component, an inorganic component and a functional component; wherein the organic component comprises polyethylene oxide, and the inorganic component comprises scandium oxide and titanium dioxide.
2. The composite battery separator according to claim 1, characterized in that: The base film includes a polyimide-polypropylene composite film.
3. The composite battery separator according to claim 1, characterized in that: The mass ratio of the organic component to the inorganic component is (3-10):(10-20); And / or, the mass ratio of the scandium oxide to the titanium dioxide is (2-5): (20-30); And / or, the mass ratio of the sum of the mass of the organic component and the inorganic component to the mass of the functional component is (25-40):(5.25-20.3).
4. The composite battery separator according to claim 1, characterized in that: The functional component includes at least one of a dispersant, a thickener, a wetting agent and a binder; Preferably, the dispersant includes at least one of polyvinyl pyrrolidone, polyacrylate, polyacrylamide and polyacrylic acid; preferably, the thickener includes at least one of hydroxymethyl cellulose, sodium hydroxymethyl cellulose, hydroxypropyl methyl cellulose and methyl cellulose; the wetting agent includes at least one of sodium butyl naphthalene sulfonate or sodium alkyl sulfate; the binder includes at least one of polyacrylic acid or polyacrylonitrile.
5. The composite battery separator according to claim 4, characterized in that: The functional components include the following components in parts by weight: 0.55 to 2.5 parts of a dispersant, 2.5 to 12 parts of a thickener, 0.2 to 0.8 parts of a wetting agent, and 2 to 5 parts of a binder.
6. The method for preparing a composite battery separator according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: A mixed dispersion of scandium oxide and titanium dioxide is prepared, and then subjected to a temperature treatment to obtain a doped inorganic powder; the doped inorganic powder and polyethylene oxide are fully mixed in an organic solvent to obtain a composite material; The composite material and the functional component are fully mixed in water to obtain a composite slurry; the composite slurry is coated on at least one side of a base film, and then vacuum dried to obtain a composite battery separator.
7. The method for preparing a composite battery separator according to claim 6, characterized in that: In the composite slurry, the mass proportion of water is 40% to 70%.
8. The method for preparing a composite battery separator according to claim 6, characterized in that: The temperature of the heating treatment is 160°C to 200°C, and the insulation time of the heating treatment is 2h to 4h; And / or, the vacuum drying temperature is 65° C. to 75° C., and the vacuum drying time is 6 h to 8 h.
9. A secondary battery, characterized in that: It comprises the composite battery separator as claimed in any one of claims 1 to 5.
10. An electrical device, characterized in that: Comprising the secondary battery as claimed in claim 9.
Citation Information
Patent Citations
Preparation method of positive electrode of transition metal doped antimonene composite lithium-sulfur battery
CN114220949A
Fiber diaphragm, preparation method thereof and application of fiber diaphragm in in-situ polymerization solid-state lithium battery
CN117594951A
Positive electrode active material and preparation method thereof
CN117712312A
Fabrication of films and coatings used to activate shear thickening, impact resistant electrolytes
US20190326632A1
Modified composite separator and preparation method therefor
WO2023066342A1
